Analisis Teknik Mesin Pencacah Plastik - wahyu kristian sugandi (Faculty of Agriculture University of Singaperbangsa Karawang, 2019)
Singaparna, Tasikmalaya can produce 154.72 m3 of plastic waste every day. The plastic waste was then managed by the Tasikmalaya Waste Bank. But the management has been only limited to sorting and finally sold at low prices to the city. To increase the sale value, the plastic waste needs to be chopped in advance so that the dealer will buy it at a high price, of course this will add income to BST. Agricultural Laboratory Equipment and Machinery FTIP Unpad had been developed a plastic waste counting machine to be applied to BST Tasikmalaya in hopes of producing the desired plastic count. However, this machine does not yet have specification data so further research is needed on technical analysis. The purpose of this research was to analyze the technique of plastic counting machines which include; driving power requirements, shaft diameter, number of transmission coir, frame analysis, and weld strength. The research method used was descriptive analysis method, which is measuring and calculating the structural components of the machine. The results of the calculation of the technical analysis showed that the driving force was 5.12 HP, shaft diameter of 28.1 mm, the number of belts used were 2 belts, frame deflection of 0.005 mm, welding strength to support the load of 504.234 N. Technically the garbage counting machine plastic can chop plastic waste well.